2018
DOI: 10.1007/s00024-018-1792-2
|View full text |Cite|
|
Sign up to set email alerts
|

Tectonic stress regime in the 2003–2004 and 2012–2015 earthquake swarms in the Ubaye Valley, French Alps

Abstract: We study two earthquake swarms that occurred in the Ubaye Valley, French Alps within the past decade: the 2003-2004 earthquake swarm with the strongest shock of magnitude ML = 2.7, and the 2012-2015 earthquake swarm with the strongest shock of magnitude ML = 4.8. The 2003-2004 seismic activity clustered along a 9-km-long rupture zone at depth between 3 and 8 km. The 2012-2015 activity occurred a few kilometres to the northwest from the previous one. We applied the iterative joint inversion for stress and fault… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
(85 reference statements)
3
10
0
Order By: Relevance
“…As shown by Leclère et al () for the 2004–2005 crisis, such heterogeneous structures, and therefore mechanisms, are not compatible with a unique, static, stress state. Fojtíková and Vavryčuk () also found that a very low friction coefficient of 0.2–0.3 is required. Therefore, either high fluid‐pressure or heterogeneous stress state are required to induce slips on badly oriented structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by Leclère et al () for the 2004–2005 crisis, such heterogeneous structures, and therefore mechanisms, are not compatible with a unique, static, stress state. Fojtíková and Vavryčuk () also found that a very low friction coefficient of 0.2–0.3 is required. Therefore, either high fluid‐pressure or heterogeneous stress state are required to induce slips on badly oriented structures.…”
Section: Discussionmentioning
confidence: 99%
“…The seismic clusters outside the main structure occurred on structures with various azimuths. By inverting focal mechanisms for the 2003–2004 crisis (Leclère et al, ) and the 2012–2015 crisis (Fojtíková & Vavryčuk, ), the stress field shows a subhorizontal minor component σ3 oriented ~N100° and a N11 to 29° σ1 component, with a plunge between 12° and 61° depending on the authors. Such stress field is compatible with slip on N160° structures, such as the deep ones.…”
Section: Discussionmentioning
confidence: 99%
“…Mathey et al (2021b) found that the extensional component is oblique to the strike of the Alpine belt, while it was assumed normal until now (Sue et al 2007). Similar stress-states have been reconstructed for the last swarms (2003-2004 and 2012-2015) occurring in the Ubaye Region (Leclère et al 2013;Fojtíková and Vavryčuk, 2018). Focal mechanisms of the largest events are from several catalogues: Fréchet and Pavoni (1979), Leclère et al (2013), Thouvenot et al (2016), FMHex20 (Mazzotti et al 2021) and Mathey et al (2021a).…”
Section: Tectonic Contextmentioning
confidence: 62%
“…In this context, we can speculate that each mainshock ruptured one of these two OOFs. Such examples have been documented in the literature (e.g., Fojtíková & Vavryčuk, 2018; Noisagool et al., 2016; Singh et al., 2017; Vavryčuk, 2011) and would favor scenario A. Nevertheless, scenario B also remains plausible, that is, stress‐favored, with both M1 and M2 rupturing close to one of the OOFs (within 30° in terms of Kagan angle) with the reactivation of a minor transversal fault of the domino domain, according to the SE side of the L‐shaped aftershock pattern.…”
Section: Discussionmentioning
confidence: 85%